1995
DOI: 10.1530/eje.0.1330598
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for oestrogenic regulation of heat shock protein expression in human endometrium and steroid-responsive cell lines

Abstract: Gene amplification with target-specific primers (reverse-transcription polymerase chain reaction (RT-PCR)) was used to monitor the relative expression of oestrogen and progesterone receptor mRNAs alongside the mRNAs for heat shock proteins HSP 90 alpha, HSP 90 beta and HSP 70a in normal samples of human endometrial tissue over the whole menstrual cycle and in short-term cultures of steroid-responsive (T47-D) and unresponsive (HRT-18) cell lines exposed to oestradiol and progesterone over a 24-h incubation peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 0 publications
3
23
0
Order By: Relevance
“…We found a significant increase in antibody response against Hsp 65 although the mechanism involved remains unclear. Nevertheless, this result agrees with a recent report demonstrating that estrogen was able to regulate the expression of Hsp (both the 90 and 70 subclasses) in human endometrium and several human cell lines (9). How antibodies against Hsp or cross-reactive antibodies against Hsp could influence the genesis and progression of CAD requires further investigation.…”
supporting
confidence: 92%
“…We found a significant increase in antibody response against Hsp 65 although the mechanism involved remains unclear. Nevertheless, this result agrees with a recent report demonstrating that estrogen was able to regulate the expression of Hsp (both the 90 and 70 subclasses) in human endometrium and several human cell lines (9). How antibodies against Hsp or cross-reactive antibodies against Hsp could influence the genesis and progression of CAD requires further investigation.…”
supporting
confidence: 92%
“…Several studies have found increased expression of Hsp70 in various hormone-treated cell types (Tang et al, 1995;Jones et al, 2000;Lu et al, 2002;Gehring, 2004). The fact that Hsp70 can completely prevent iA␤ 1-42 -mediated toxicity indicates only that Hsp70 is sufficient for neuroprotection against iA␤ 1-42 toxicity but does not rule out the possibility that other effects of the steroid hormones on neurons could also be neuroprotective.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of estrogen to alter levels of the uterine hsp90 isoforms hsp90α and hsp90β has been demonstrated previously (Shyamala et al 1989). Estrogen also regulates mRNA levels of uterine hsp70 (Rivera-Gonzalez et al 1998;Tang et al 1995;Wu et al 1996), hsp90, and grp94 (Shyamala et al 1989).…”
mentioning
confidence: 78%